Cumulative physical activities as correlates of fitness and health status of secondary school students (2011)
Fundamental motor skill ability has been found to be positively related to performance in physical activity. Physical inactivity on the other hand, has [become a major public health concern, contributing to the chronic, non-communicable disease, epidemic. The rate of inactivity and lack of physical fitness prevalent in adolescents most often result in cardiovascular diseases which, had led to deaths of many adolescents at their prime age due to heart failure attributed to poor fitness and health. This study, therefore, assessed the) impact of cumulative physical activities, Health Enhancing Physical Activity (HEPA) and Recreation and Light Physical Activity (RLPA) on the fitness and health status of secondary school students. This study was a correlational type. A multi-stage sampling technique was employed in selecting two local governments, ten schools and 170 senior secondary school-students from Ibadan North and Ibadan North East Local Government Areas, Oyo State. The fort instruments used for data collection to answer the seven research questions, using test-retest reliability coefficient were: Exercise, Recreation and Sports Survey Questionnaire (r=0.82), Physical Activity Classification Questionnaire (r = 0,74). Anthropometric and Blood Pressure Characteristics Package (r = 0.80) and Fitness Test of Battery Package (r - = 0.68). Data were analyzed using mean, percentages and multiple regressions. The level of significance was set at P<0.05. Gender, HEPA and RLPA showed no significant influence, while age had a significant relative influence on body composition, (β=17, t = 2.20; P<0.05). There was a significant relationship of cumulative physical activity on physical fitness (r = .03; P<0.05). Moreover, only gender had significant relationship on physical fitness (β = -3.04, P<0.05). There was a significant relationship of cumulative physical activity and blood pressure (r = 0.015; P<0.05). There was an inverse relationship between body mass, age, gender and physical activities, while physical fitness increases in relation to increased physical activity.